(untitled) (Scientia Agropecuaria, 2023)
The reaction between starch granules and octenyl succinic anhydride (OSA) is regularly retarded due to the low breakthrough of large oily OSA droplets into starch granules in an aqueous reaction system. Furthermore, high-speed shearing is widely used in the food industry, demanding high shear, cavitation, and collision force. In this sense, high-speed shearing could reduce the size of OSA droplets and promote a more homogeneous distribution of groups in the starch granule. The aim of this study was to evaluate the impact of OSA potato starch synthesis assisted by high-speed shear on structure (SEM and FTIR), gelatinization, rheology, and emulsifying activity (ES and AS) was investigated. The results showed a gradual increase in DS proportional to the applied speed. Likewise, the OSA starches showed a slight alteration in the shape of the granules (SEM), and FT-IR spectroscopy showed a characteristic absorption of the ester carbonyl groups in the OSA starch at 1724 cm-1. The high-speed shear-treated starches exhibited a significant change in the reduction of the initial gelatinization temperature, although not in the enthalpy. All the gels presented rheology adjusted to the Herschel-Bulkley model with variations in the initial shear stress. Changes in the viscoelastic behavior are proportional to the shear rate detected. High-speed shear treatment did not show a significant effect on emulsion stability (ES) and emulsion activity (EA). Consequently, applying high shear rates allows having OSA starches with different uses.